THE EFFECT OF SPIRITUALITY IN PROMOTING SUSTAINABLE BEHAVIOUR AMONG STUDENTS IN PUBLIC UNIVERSITIES IN MALAYSIA (Journal of Technology and Operations Management, 2019)
The purpose of the study is to examine the predictors that influencing sustainable behaviour among students in public universities in Malaysia. For this reason, this paper seeks to address the research problem about the issue of the sustainability development due to the behaviour problems regarding the environmental issues. In the current globalization arena, government of each countries facing challenges and keep on finding the better ways to manage environmental problems that occurred in Malaysia and enhance sustainable behaviour among societies. For that governments in each countries including Malaysia have been spent huge amount of money for the development and program that increase awareness and knowledge among them. At this vein, investigation on factors that sustainable behaviour is important. Previous studies show little evidence about the relationship between sustainable behaviour and spirituality. Thus, this study found that spirituality plays effective role in influencing sustainable behaviour among students. Therefore, this study is the conceptual paper that addressing the effect of spirituality and knowledge in influencing sustainable behaviour among students